Influence of plug cell volume and substrate type on the development of cucumber seedlings for transplanting (International Journal of Technology and Management Research, 2020)
This study investigated the influence of plug cell volume ( 72 cell ( 36 mL ) and 128 cell tray ( 20 mL) ) and substrate type ( peat and cocopeat) on the development of cucumber seedlings. The experiment was designed in a factorial arrangement in a completely randomized design with four replications. The following growth data were measured: plant height, number of leaves, stem diameter and shoot and root biomass. The result showed significant differences among the treatments with respect to the plant height, stem diameter, as well as the shoot and root biomasses. Overall, it was found that growing cucumber seedlings in 36 mL cell volume with cocopeat produces a much better young plants for transplanting.